The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/jp804578d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Gas-Phase Chemiionization Reactions La + O and La + O2

Abstract: The La + O and La + O 2 chemiionization reactions have been investigated with quantum chemical methods. For La + O 2 (X 3 Σ g ) and La + O 2 (a 1 ∆ g ), the chemiionization reaction La + O 2 f LaO 2 + + e -has been shown to be endothermic and does not contribute to the experimental chemielectron spectra. For the La + O 2 (X 3 Σ g ) reaction conditions, chemielectrons are produced by La + O 2 f LaO + O, followed by La + O f LaO + + e -. This is supported by the same chemielectron band, arising from La + O f LaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…The CD-CASPT2 values are R e = 1.855 Å and e = 803 cm −1 , respectively, in excellent agreement with Ref. 35. With 40% truncation, FNO-CASPT2 introduces a negligible error in the computed equilibrium distance ͑R e = 1.859 Å͒ and predicts a relatively accurate frequency of e = 759 cm −1 .…”
supporting
confidence: 84%
See 3 more Smart Citations
“…The CD-CASPT2 values are R e = 1.855 Å and e = 803 cm −1 , respectively, in excellent agreement with Ref. 35. With 40% truncation, FNO-CASPT2 introduces a negligible error in the computed equilibrium distance ͑R e = 1.859 Å͒ and predicts a relatively accurate frequency of e = 759 cm −1 .…”
supporting
confidence: 84%
“…Spectroscopic constants of LaO n and LaO n + "n =1,2… An account on the mechanisms of La+ O and La+ O 2 chemionization reactions studied at the CASSCF/CASPT2 level of theory was recently given by Todorova et al 35 In the present work, spectroscopic constants of LaO n and LaO n + ͑n =1,2͒ are reproduced by employing FNO-CASPT2, in order to understand the reliability and the limits of this method. For consistency of the results, we employ the same basis sets ͑ANO-RCC of quintuple-quality͒, active spaces, geometries as in the previous study.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent publication, the chemiionization reactions that occur for the La + O( 3 P), La + O 2 (X 3 Σ italicg), and La + O 2 (a 1 Δ g ) reaction conditions have been established by quantum chemical methods 1. It has been shown that for La + O 2 (X 3 Σ italicg) and La + O 2 (a 1 Δ g ), the chemiionization reaction La + O 2 → LaO 2+ + e − is endothermic and does not contribute to the experimental chemielectron spectra.…”
Section: Introductionmentioning
confidence: 99%